2010
DOI: 10.1111/j.1365-2966.2010.17990.x
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of the H ii regions in the extended ultraviolet disc of NGC 4625

Abstract: Using deep Subaru/Faint Object Camera And Spectrograph (FOCAS) spectra of 34 H ii regions in both the inner and outer parts of the extended ultraviolet (XUV) disc galaxy NGC 4625 we have measured an abundance gradient out to almost 2.5 times the optical isophotal radius. We applied several strong line abundance calibrations to determine the H ii region abundances, including R23, [N ii]/[O ii], [N ii]/Hα as well as the [O iii] λ4363 auroral line, which we detected in three of the H ii regions. We find that at t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 59 publications
(148 reference statements)
5
57
1
Order By: Relevance
“…In addition, when the observations are deep enough to investigate the outskirts of galaxies, it has been often found that the metallicity tends to reach a plateau: in external galaxies whose gradients are marked by H ii regions Goddard et al 2011;Werk et al 2011) and in our own Galaxy using open clusters (Sestito et al 2006;Magrini et al 2009a;Lépine et al 2011), H ii regions (Vilchez & Esteban 1996), and PNe (Maciel & Quireza 1999) 1 . If we focus on regions within the galactic optical radius, where the gradients are clearly negative, the most important open questions are: How was the present time radial gradient established?…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when the observations are deep enough to investigate the outskirts of galaxies, it has been often found that the metallicity tends to reach a plateau: in external galaxies whose gradients are marked by H ii regions Goddard et al 2011;Werk et al 2011) and in our own Galaxy using open clusters (Sestito et al 2006;Magrini et al 2009a;Lépine et al 2011), H ii regions (Vilchez & Esteban 1996), and PNe (Maciel & Quireza 1999) 1 . If we focus on regions within the galactic optical radius, where the gradients are clearly negative, the most important open questions are: How was the present time radial gradient established?…”
Section: Introductionmentioning
confidence: 99%
“…Although the surface brightness does not show any flattening associated with the oxygen abundances, colors also have a U-shape at the outer regions of disks, especially for galaxies with masses similar to the Milky Way (MW). In addition, several investigations both in our MW (Vilchez & Esteban 1996) and in nearby galaxies (Bresolin et al 2009(Bresolin et al , 2012Rosales-Ortega et al 2011;Goddard et al 2011;Marino et al 2012;Sánchez et al 2012b) have reported a shallower oxygen abundance gradient (or flattening) in the outskirts, beyond ∼2 effective radii, R eff . In general, these deviations to the universal abundance gradient are explained in terms of variations of the in situ gas density or effective SF history, the presence of a bar, or coincidence with the corotation radius.…”
Section: Introductionmentioning
confidence: 99%
“…but without the depth needed for precise color measurements in the outer disk (Swaters & Balcells 2002;Gil de Paz et al 2005). Abundances indicate a discontinuity in metallicity at R 25 and a nearly constant outer disk abundance of ∼0.2 Z (Goddard et al 2011).…”
Section: Ngc 4625mentioning
confidence: 99%
“…inner disk until it is no longer detected. For comparison we plot the gas phase metallicity gradient measured by Goddard et al (2011), which, like the multi-wavelength profiles, shows a break at the edge of the inner disk.…”
Section: Multi-wavelength Profilesmentioning
confidence: 99%
See 1 more Smart Citation